Effectiveness of Using E-assessment Model Toward Students Understanding in Mechanics Concept - Hairunisyah Sahidu; Gunawan Gunawan; Ni Made Yeni Suranti; Nina Nisrina; Imran Imran (Department of Physics Education, Universitas Mataram, 2020)
One of the ways to use technology in education is in the assessment process, namely e-assessment. E-assessment is a system designed to make the process more effective and efficient in terms of time, funds and assessment achievements. In this study, an e-assessment has been developed which is oriented towards students understanding. The purpose of this research is to determine the effectiveness of using e-assessment on students understanding. The research method used was a quasi-experimental in the pretest posttest group design. Students understanding data were obtained from a multiple-choice test with 25 questions related to the concept of mechanics. The data obtained were analyzed for the increase with the gain normalization equation. The results obtained indicate that the developed e-assessment model can improve students understanding with the medium improvement category. The increase in students' understanding of concept in the cognitive aspects of C1, C2 and C3 was in the high category of increase and aspects of C4, C5, and C6 increased with the category of moderate improvement.